International social work issues, strategies, and programs - Cox, David R (David Ray); Pawar, Manohar S. (SAGE Publications, 2013)
A rapidly growing number of social workers are expressing a deep interest in and strong concern for global situations adversely affecting the well-being of millions of people. Such situations include global poverty, widespread conflict and post-conflict reconstruction, and the large population of displaced persons, and vulnerable and marginalized groups within them. Increasingly practitioners from several professions are actively involved in addressing these issues at local, national and international levels. This book aims to encourage and inform such involvement by drawing together the practice wisdom gradually emerging within the broad scope of international social work practice. Utilizing an integrated perspectives approach incorporating global, human rights, ecological and social development perspectives, the text is designed to prepare social workers, human services professionals, development practitioners